HIGHER EDUCATION ROLES TO SUPPORT CLIMATE CHANGE MITIGATION - M Suteki; S Betlajery; J R Kuntag (Universitas Tadulako, 2023)
Climate change has become an issue that affect every aspect of our lives, including in food security and economic matters. Climate change mitigation plays a key role to prevent the worst impact of climate change. Higher education can take a role on university-based mitigation action in reducing local emission by promoting service-learning approaches that include climate change mitigation. This paper aims to explore the role of higher education to support climate change mitigation to achieve tangible local benefits in facing climate change. This research uses a systematic literature review method related to climate change mitigation in higher education. This paper illustrating the role of higher education to support climate change mitigation by using service-learning approach and creating climate change governance networks. Higher Education Institution as an organization with significant impact toward local community can act as catalyst for sustainable development system. Higher education institution needs to regulate and renew energy systems and reorganize transportation system in order to reduce CO2 emissions and communicate message to higher education community to support climate change mitigation actions in personal level.